Role of ultrasonography in evaluation of various causes of pelvic pain in first trimester of pregnancy - Gurung, Kismat; Sharma, Keshab; Sharma, Pujan (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Pelvic pain in early pregnancy presents a diagnostic challenge due to overlapping physiological and pathological causes. Ultrasonography is the primary modality for prompt and accurate diagnosis. The aim of this study was to evaluate the role of ultrasonography in determining the underlying causes of pelvic pain in first trimester pregnancies.Methods: A hospital-based cross-sectional study was conducted from April 2023 to September 2024 at the Radiology Department of Gandaki Medical College, Pokhara. A total of 87 pregnant women presenting with pelvic pain in their first trimester were evaluated using abdominal ultrasonography; transvaginal scans were performed when required.Results: Among the 87 pregnant women presenting with first-trimester pelvic pain, the mean age was 28.5±6.2 years (range 20–45 years), with most participants between 20 to 29 years. Nearly one-third were primigravida, and 35(40.2%) were nulliparous. A history of pelvic surgery was reported in 18(20.7%) of cases. The most frequent cause of pelvic pain was normal pregnancy 45(51.7%), followed by ectopic pregnancy 21(24.1%), abortion 12(13.8%), blighted ovum 3(3.4%), and simple ovarian cyst (22.3%). Less common causes included acute appendicitis, dermoid cyst, fibroid uterus, and distal ureteric calculus 1(1.1% each).Conclusions: Ultrasonography is an essential first-line imaging modality in the evaluation of pelvic pain in early pregnancy. It enables accurate differentiation between viable pregnancy, pregnancy loss, and non-obstetric causes, guiding timely management and improving maternal outcomes.